2014
DOI: 10.1016/j.jaci.2013.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell NKG2D and granzyme B are critical for allergic pulmonary inflammation⋆

Abstract: BackgroundThe diverse roles of innate immune cells in the pathogenesis of asthma remain to be fully defined. Natural killer (NK) cells are innate lymphocytes that can regulate adaptive immune responses. NK cells are activated in asthma; however, their role in allergic airway inflammation is not fully understood.ObjectiveWe investigated the importance of NK cells in house dust mite (HDM)-triggered allergic pulmonary inflammation. Specifically, we aimed to determine the role of the major NK-cell activating recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 63 publications
0
48
1
Order By: Relevance
“…NK cells have been shown to be capable of augmenting or suppressing the development of allergic lung inflammation (15, 17, 36). We thus evaluated whether the presence of increased numbers of pNK cells evident in the IP −/− mice impacts lung mucosal immune responses in these animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells have been shown to be capable of augmenting or suppressing the development of allergic lung inflammation (15, 17, 36). We thus evaluated whether the presence of increased numbers of pNK cells evident in the IP −/− mice impacts lung mucosal immune responses in these animals.…”
Section: Resultsmentioning
confidence: 99%
“…NK cells residing in the lung mucosal tissue have been described previously, however, their relationship to conventional circulating NK cells remains unclear (1113). Previous reports have investigated the effect of NK cells on allergic lung inflammation with contradictory findings, with some instances inhibiting allergic lung inflammation (14, 15) and in others promoting eosinophilic inflammation (16, 17). Importantly, NK cells are responsive to a range of endogenously produced eicosanoids which include Resolvin-E1 (18), Lipoxin-A4 (19), PGD 2 (20), PGE 2 (21) and leukotrienes (22).…”
Section: Introductionmentioning
confidence: 99%
“…NK cell recruitment and activation is primarily mediated by epithelial cell release of IL-15, which increases in the nasal mucosa within a few days after HRV challenge 137 . The relevance of this response to post-viral airway disease is uncertain, but NK cell expression of NK group 2 member D (NKG2D; also known as KLRK1) and granzyme B was required for the allergic response to house dust mite extract in mice 138 . Other work showed that IL-17-producing LIN − THY1.2 + ILC3s were required for airway hyperreactivity in a mouse model of asthma that was associated with obesity 139 .…”
Section: Innate Immune Cellsmentioning
confidence: 99%
“…A manuscript by Farhadi et al provided insight into mechanisms of NK cell activation by allergens [13]. The investigators started their story by demonstrating that that airway inflammation in the house dust mite (HDM)-induced model of asthma was dependent on NKG2D.…”
Section: Nk Cells In Mouse Models Of Asthmamentioning
confidence: 99%